Validation of Difficult Airway Physiological Score (DAPS) in Critically Ill Adults Undergoing Endotracheal Intubation in the Emergency Department - Shahan Waheed; Junaid Abdul Razzak; Nadeem Ullah Khan; Ahmed Raheem; Asad Iqbal Mian (Emergency Medicine International)
Background. Critically ill patients have increased risk of cardiovascular collapse following endotracheal intubation due to physiological instability. This study aims to validate the Difficult Airway Physiological Score (DAPS) in adults to predict the risk of serious outcomes in the emergency department of a tertiary care private hospital. Methods. This is a cohort study conducted in the emergency department (ED) from 2021 to 2022. Difficult Airway Physiological Score (DAPS) was derived from a sample of 1021 patients through a retrospective study. The variables in the score were age, gender, time of intubation, vitals and vomiting at presentation, pH <7.3, fever, physician’s anticipation for patient decline, and agitation. The model performance was assessed prospectively on a separate dataset (n = 326) using train-test split method. Postintubation desaturation, hypotension, cardiac arrest, and mortality postintubation were the serious outcomes. ROC analysis, sensitivity, specificity, PPV, and NPV were used to assess score validity. Results. Our study includes 326 patients, of which 123 (37.7%) were males and 203 (62.2%) were females. The sample was divided into high-risk (DAPS ≥10) group, n = 194 with mean age of 52 (SD = ±18) years, and low-risk (DAPS <10) group, n = 132 with mean age of 47.7 (SD = ±17.4) years. The shock index ≥0.9 was in 128 (66%), while it was <0.9 in low-risk n = 111 (84%), p value <0.001. Similarly, pH <7.3 was seen in 70 (36.1%) in high-risk group compared to 4 (3%) in low-risk group, p value <0.001. Cardiac arrest was observed in 56 (17.2%) patients, of which 45 (23.2%) were in high-risk and 11 (8.3%) in low-risk groups (p<0.001). Hypotension was the primary outcome in the high-risk group 100 (51.5%) versus 32 (24.2%) in low-risk group (p<0.001). The DAPS of 10 had an area under the curve of 0.865 (0.71–0.84). The sensitivity of DAPS was 78.5%, specificity 77.9%, and accuracy 78.2%. Conclusion. The score can accurately predict serious outcomes in critically ill adult patients with physiologically difficult airway demonstrating good sensitivity and specificity.